Combined AFP-CRUT with microvascular invasion accurately predicts mortality risk in patients with hepatocellular carcinoma following curative liver resection. (August 2015) - Huang, Gui-Qian; Zhu, Gui-Qi; Huang, Sha; You, Jie; Shi, Ke-Qing; Hu, Bin; Ruan, Lu-Yi; Zhou, Meng-Tao; Braddock, Martin; Zheng, Ming-Hua
Abstract : Aims: To establish and validate an equation of α-fetoprotein (AFP) change rate over unit time (AFP-CRUT) as a potential predictor of survival after resection in patients with hepatocellular carcinoma (HCC). Methods: The AFP-CRUT was constructed based on dynamic variation in AFP over time and then categorized into quintiles. The area under the receiver operating characteristic (ROC) curve showed the performance for survival prediction. Results: As independent risk factors associated with mortality, microvascular invasion (MVI) (p = 0.003) and AFP-CRUT quintiles (p = 0.048) were combined to enhance the predictive effect. The highest 5-year overall survival rate following curative liver resection (93%) was observed in patients with MVI absent and AFP-CRUT in quintile 1 (49.64 to 209.61). In contrast, the lowest 5-year overall survival (7%) was obtained in quintile 5 (−469.29 to 6.45) with MVI present. In validation cohorts at both 12 and 24 months, AFP-CRUT performed well as a potential prognostic biomarker. Conclusions: Combining AFP-CRUT quintiles with MVI may predict significantly improved outcomes and enhance the predictive power for patient responses to therapeutic intervention.